Discours direct : syntaxe et prosodie - Sylvie HANOTE (E-REA)
This paper investigates the intonational phrasing of reporting clauses. It is based on the acoustic analysis of an oral corpus drawn from the radio (BBC Radio for British English and National Public Radio for American English) which has been compiled at Poitiers University and contains about 8 hours of audio files (= ca 80,000 words) from various types of documents (political speeches, interviews, news broadcasts, scientific programmes…), most of them recorded from 2004 to 2013. The main objective is to see what parameters –if any- have a decisive influence on the change in the level of utterance. To do so, the paper closely investigates the different acoustic behaviours of reporting speech clauses depending on their position in the utterance (initial, medial or final), on the internal word order (SV or VS) and on the type of syntactic subject of the reporting verb.